An Acute Transition from Rearfoot to Forefoot Strike does not Induce Major Changes in Plantarflexor Muscles Activation for Habitual Rearfoot Strike Runners. - Kovács, Bálint; Petridis, Leonidas; Négyesi, János; Sebestyén, Örs; Ye Jingyi; Jingfeng Zhang; Yaodong Gu; Tihanyi, József (Journal of Sports Science & Medicine, 2023)
Footstrike pattern has received increased attention within the running community because there is a common belief that forefoot strike running (FFS) is more advantageous (i.e., improve performance and reduce running injuries) than rearfoot strike running (RFS) in distance running. Literature reports suggest greater knee joint flexion magnitude and initial knee angle during stance in FFS compared with RFS running We examined the EMG activation of the triceps surae muscles during an acute transition from RFS to FFS strike. We tested the hypothesis that due to larger knee flexion in FFS the gastrocnemius muscles possibly decrease their EMG activity because muscle fascicles operate under unfavorable conditions. Fourteen competitive healthy middle- and long-distance runners who were habitual RFS runners ran on a treadmill at three speeds: 12, 14, and 16 km.h-1. Each running speed was performed with both FFS and RFS patterns. Lower limb kinematics in the sagittal plane and normalized electromyography (EMG) activity of medial gastrocnemius proximal, middle and distal regions, lateral gastrocnemius and soleus muscles were compared between footstrike patterns and running speeds across the stride cycle. Contrary to our expectations, the knee joint range of motion was similar in FFS and RFS running. However, the sagittal plane ankle joint motion was greater (p < 0.01) while running with FFS, resulting in a significantly greater muscle- tendon unit lengthening (p < 0.01) in FFS compared with RFS running. In addition, medial and lateral gastrocnemius showed higher EMG activity in FFS compared with RFS running in the late swing and early stance but only for a small percentage of the stride cycle. However, strike patterns and running speed failed to induce region-specific activation differences within the medial gastrocnemius muscle. Overall, well-trained RFS runners are able to change to FFS running by altering only the ankle joint kinematics without remarkably changing the EMG activity pattern.